Investigation of dielectric properties of 5CB and chiral pyridine based liquid crystal composites - Canli, N. Yilmaz; Vardar, D.; Kavak, P.; Uyunmaz, M.; Kilic, H. Akdas; Ocak, H.; Eran, B. Bilgin (INDIAN ASSOC CULTIVATION SCIENCE, 2025)
Liquid crystals (LCs) are materials that are becoming increasingly important due to their applications such as liquid crystal displays and many other applications. Only one LC cannot meet all the parameters required for applications. This study focused on investigating changes in dielectric properties with mixtures of LCs at different concentrations. The dielectric characterization of liquid crystal composites 5CB (4-cyano-4'-pentylbiphenyl) doped with LC1 ((S)-4-(3,7-Dimethyloctyloxy)phenyl 6-(4-dodecyloxyphenyl)pyridine-3-carboxylate) and LC2 ((S)-4-(2-Methylbutoxy)phenyl 6-(4-dodecyloxyphenyl)pyridine-3-carboxylate) and at 2 and 5 wt%) were investigated. Dielectric parameters (epsilon ', epsilon '', triangle epsilon s) of 5CB, 5CB+(2wt.%)LC1, 5CB+(5wt.%)LC1, 5CB+(2wt.%)LC2, 5CB+(5wt.%)LC2 have been calculated. The LC1 and LC2 compounds exhibit the SmC* and SmA mesophases. In our study, it was observed that the addition of LC1 and LC2 to 5CB increased the mobility of polar molecules, which increases the dielectric strength (triangle epsilon s).
Keywords: Liquid crystal; Dielectric parameters; Composites; Dielectric strength; AC-CONDUCTIVITY; Physics